Southwest Research-Extension Center, Field Day 2004 (Kansas Agricultural Experiment Station Research Reports, 2004)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: 2004; SRP927; crops; tillage; weed science; insects control